Single and combined soliton solutions to a system of coupled nonlinear Schrodinger type equations by using two analytical approaches - Aliyu, Aliyu Isa; İnç, Mustafa; Yusuf, Abduilahi (Amer Scientific Publishers, 2018)
This paper obtains the soliton solutions of a system of coupled nonlinear Schrodinger type equations (CNLSE). Two analytical approaches, namely; the sine-Gordon expansion method (SGEM) and the generalized tanh (GTH) method are used to extract the kink-type, bell-shaped, kink-bell shaped, singular and combined solitons.
Keywords: Sine-Gordon Expansion Method; Soliton Solutions; Coupled Nonlinear Schrodinger Type Equation